THE FIGHT OF PATIENT WITH PARANOID SCHIZOPHRENIA DISORDER WITH HIS THE PSYCHIATRIC DIAGNOSIS: A GAME OF "EVERYTHING OR NOTHING" - Trifu, Simona; Popescu, Alexandra; Dragoi, Ana Miruna (International Journal of Research -GRANTHAALAYAH, 2019)
Introduction: "Blue whale challenge" is a large social media phenomenon believed to have originated in Russia in 2015. It is supposed to be a "game" in which the "player" receives 50 tasks from an online administrator. Initial tasks are more inclined towards self-harm and antisocial behavior, the final task being suicide. The name is thought to be derived from "failed whales" that suggest suicide. Motivation: Although the target audience of this outrages game is mainly adolescents; it has proven to be eminently more harmful among psychiatric patients, of all ages, especially those with psychotic disorders. When psychosis overlaps with an already dangerous online "game", the risks are heightened. Objectives: Our case study intends to highlight the risks of a 35-year-old patient, a former police officer, diagnosed with paranoid schizophrenia about 15 years ago, difficult to control from therapeutic point of view, which is completely immersed in this "game", in which the tasks are on the border between concrete and delirium. Methods: Emergency psychiatric hospitalization, medical supervision, daily psychiatric monitoring, psychological evaluation, psychodynamic interview, case study. Results: The patient deliriously interprets the rules of the game his current task is to go to three different psychiatrists and to prove his health in order to "release" him from his diagnosis of paranoid schizophrenia. He motivates the objective of the challenge with the Blue Whale the "liberation of the soul", the alternative being suicide. He plays "all or nothing", there are no differences in shades between "Beware of donkeys" (children’s game), "Blue whale" and "Russian roulette" (games for real men). The patient himself sees either the garbage man who deserves the lethal injection, or Jesus capable of winning the game. His thinking is dominated by the conflict between the concrete and the abstract; the secret of the paranoid patient being the emphatic ability to transform his powerlessness into "I am invincible!", because for this patient "at first it was the word". When he spoke about his previous tasks, he confessed many acts of violence, pseudo- reminiscence with delirious integration in the form of confabulations. In addition, he believes that everyone receives orders from the Blue Whale, including medical staff, which makes difficult to establish a doctor-patient relationship.